DIOXINS / FURANS (PCDDs/PCDFs) CONTROL IN CEMENT INDUSTRY IN ROMANIA - CRISTIAN CIOBANU; GHEORGHE VOICU; MAGDALENA-LAURA TOMA; SILVIU MARCU (Journal of Engineering Studies and Research)
The most important sources of dioxins are waste incineration, industrial (dioxins are by-products), volcanic eruptions, fire, etc. The Romanian law 278/2013 provides the air emissions limit of 0.1 ng/Nm3 gases for dioxins and furans emitted by the incineration and co-incineration plants. Some aspects regarding the control of these substances in the gases from a cement factory in Romania are presented in this paper. In incineration plant were used various fuels. However, the substances level mentioned above was within the allowed limits.